The Impact of Indonesia Netizens on Justice and Law Enforcement: Maslahah Mursalah Perspective - Yasir, Alan Maulana; Muhlis, An'nas; Karimuddin, Karimuddin (Al Ahkam, 2024)
Law has the aim of creating order and regularity which includes elements of law enforcement, and society. While harmonization is expected to proceed smoothly, the actual situation differs. People as justice seekers who have no authority and power, they can only rely on social media to get the attention of the government and the wider community to uphold justice from irregularities that occur in the realm of public law and courts. The research methodology involves using qualitative methods with an empirical approach. The results of the study will reveal from some public realities negative hashtags for law enforcement and courts that are deliberately viralized by the public to get justice. Public efforts using social media are very effective and able to change normative matters that are slow and not transparent, so that they become fast and build criticism for law enforcement for irregularities that occur in public spaces. It can even help and reveal some facts that occur and are experienced by the community in order to avoid abuse of authority over conflicts of interest in the legal realm in order to create just legal goals. The hashtag no viral no justice has emerged as a public response to legal irregularities. It is evaluated based on national law and the principles of Islamic law, playing a crucial role in assessing the boundaries of legal norms in Indonesia.